Density-dependent coupling constants and charge symmetry breaking - Barreiro, L. A. (World Scientific Publ Co Pte Ltd, 2001)
The effect of the medium in the coupling constants implicate in a charge symmetry breaking on nuclear interactions. The amount of energy due to this modification can explain the Nolen-Schiffer anomaly.